2009
DOI: 10.1097/mlr.0b013e31818afbf9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Medicare Home Health Care Market

Abstract: These results demonstrate the direct impact of policy changes on the home health care market and highlight the need to evaluate policy changes to understand both intended and unintended impacts on health markets. Future research should analyze the effect of these policy changes on other healthcare providers and systems and their impact on health outcomes for Medicare beneficiaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…Other sources have shown that for-profit establishments in both home health and hospice care sectors have entered the market in greater numbers since 2000 (3,11 In contrast, the average number of current hospice care patients served by a hospice care only agency continuously increased during 1996-2007. The number of hospice care patients served by hospice care only agencies and mixed agencies was basically similar in 1996.…”
Section: Changes In Services Provided By Mixed Agenciesmentioning
confidence: 99%
See 4 more Smart Citations
“…Other sources have shown that for-profit establishments in both home health and hospice care sectors have entered the market in greater numbers since 2000 (3,11 In contrast, the average number of current hospice care patients served by a hospice care only agency continuously increased during 1996-2007. The number of hospice care patients served by hospice care only agencies and mixed agencies was basically similar in 1996.…”
Section: Changes In Services Provided By Mixed Agenciesmentioning
confidence: 99%
“…In particular, studies on Medicare-certified home health care agencies suggest that the decreases in the number of agencies and the number of patients served while undergoing the two BBA-mandated payment system changes (i.e., interim payment system in 1997, PPS in 2000) occurred primarily among for-profit establishments (11,13).…”
Section: Changes In Services Provided By Mixed Agenciesmentioning
confidence: 99%
See 3 more Smart Citations